(untitled) (Ustozlar uchun, 2026)
This article presents a comprehensive ontological and existential analysis of Aleksandr Faynberg’s poem “YAPONIYA” (“Japan”). Employing hermeneutic, phenomenological, and semiotic approaches, the study explores the poem’s compositional structure, the lyrical subject’s inner reflections, the phenomenology of Japanese space (islands, ocean, and dawn), archetypal symbolism (samurai, Tokuboku, umbrellas), and sensory perception (sight, smell, touch, perception of light). Temporal consciousness is examined as the interplay of ephemeral phenomena and enduring cultural legacy.